Convergence Analysis of Batch Gradient Algorithm for Three Classes of Sigma-Pi Neural Networks - Zhang, Chao; Wu, Wei; Xiong, Yan (Neural processing letters, 2007)
Sigma-Pi (Σ-Π) neural networks (SPNNs) are known to provide more powerful mapping capability than traditional feed-forward neural networks. A unified convergence analysis for the batch gradient algorithm for SPNN learning is presented, covering three classes of SPNNs: Σ-Π-Σ, Σ-Σ-Π and Σ-Π-Σ-Π. The monotonicity of the error function in the iteration is also guaranteed.